Searching for Normal in the Wake of the Liberian War - Abramowitz, Sharon Alane (Book collections on Project MUSE., 2014)
Sharon Alane Abramowitz examine how humanitarian healthcare dealt with mental health and psychiatry during Liberia's turbulent postwar transition, looking closely at the ways mental health and psychosocial interventions worked to manage trauma and produce postwar peace.